Childhood Maltreatment Is an Independent Risk Factor for Prediabetic Disturbances in Glucose Regulation - Li Li; W. Timothy Garvey; Barbara A. Gower (Frontiers in Endocrinology, 2017)
AimsChildhood maltreatment (CM) is shown to be associated with obesity and depression. However, the relationship of CM to prediabetic state is much less studied. We tested the hypothesis that CM increases the risk for prediabetic state due to glucose intolerance, reduced insulin sensitivity, and beta cell function.MethodsOral glucose tolerance test (OGTT)-derived metabolic parameters of glucose tolerance, insulin sensitivity, and beta cell function were measured in 121 participants aged 19–60 years. CM exposure was measured using the Childhood Trauma Questionnaire. Blood samples were collected to measure the inflammatory factors.ResultsAfter controlling for age, race, gender, education, and depression, about 15% higher glucose area under the OGTT curve was observed in the CM group. CM individuals also exhibited impaired insulin sensitivity manifested by the Matsuda index and homeostasis model assessment of insulin resistance, which were correlated with CM severity after adjusting for depression. CM group showed approximately 50% lower disposition index. C-reactive protein and tumor necrosis factor-α levels were greater in the CM group vs. the non-CM group, and both were correlated with CM severity (r = 0.21, 0.23, respectively, both p < 0.05). Multiple regression analyses revealed that CM contributed to reduced insulin sensitivity and lower disposition index independent of depression and visceral fat mass.ConclusionThese data suggest an important relationship between CM and increased risk for prediabetic state due to glucose intolerance, impaired insulin sensitivity, and beta cell function. Our findings indicate that CM appears to be an independent risk factor for developing prediabetes.